Chemical proteomics tracks virus entry and uncovers NCAM1 as Zika virus receptor - Srivastava, Mayank; Zhang, Ying; Chen, Jian; Sirohi, Devika; Miller, Andrew; Zhang, Yang; Chen, Zhilu; Lu, Haojie; Xu, Jianqing; Kuhn, Richard J.; Andy Tao, W. (Nature communications, 2020)
The outbreak of Zika virus (ZIKV) in 2016 created worldwide health emergency which demand urgent research efforts on understanding the virus biology and developing therapeutic strategies. Here, we present a time-resolved chemical proteomic strategy to track the early-stage entry of ZIKV into host cells. ZIKV was labeled on its surface with a chemical probe, which carries a photocrosslinker to covalently link virus-interacting proteins in living cells on UV exposure at different time points, and a biotin tag for subsequent enrichment and mass spectrometric identification of the receptor or other host proteins critical for virus internalization. We identified Neural Cell Adhesion Molecule (NCAM1) as a potential ZIKV receptor and further validated it through overexpression, knockout, and inhibition of NCAM1 in Vero cells and human glioblastoma cells U-251 MG. Collectively, the strategy can serve as a universal tool to map virus entry pathways and uncover key interacting proteins. The mechanism underlying the cellular entry of Zika virus is not fully understood. Here, the authors use a chemically modified virus and time-resolved proteomics to capture interacting host proteins during virus entry and identify NCAM1 as a ZIKV receptor.